Influence of chitosan addition on the properties and characteristics of acrylic acid-chitosan based superabsorbent prepared through gamma irradiation technique and its application for urea loading - Jayanudin, Jayanudin; Lestari, Retno Sulistyo D.; Barleany, Dhena Ria; Pitaloka, Alia Badra; Yulvianti, Meri; Demustila, Harly; Yulianto, Amin; Anggoro, Dendy Vito; Ruhiatna, Adam (Jurnal Teknika, 2023)
Superabsorbent can be used as a carrier for urea-fertilizer which can release urea slowly and can be used as a dry soil moisturizer. The main goal of the current study was to investigate the influence of adding chitosan grafted onto acrylic acid as a superabsorbent base material on the properties and characteristics of the resulting superabsorbents. The method used to prepare the superabsorbent was the gamma irradiation technique. Acrylic acid was neutralized by adding KOH, and then chitosan was added. The mixture was put in a plastic container, followed by irradiation with gamma rays. The formed superabsorbent was washed and dried in an oven, then the dry superabsorbent was analyzed for its properties and characteristics. The results showed that superabsorbent properties such as swelling ratio (from 49.38 g/g to 49.38 g/g), water retention (0.43%-0.89% after 7 days), and urea loading (86.75% to 96.4%) were affected by the amount of chitosan added. However, adding too much chitosan can reduce the superabsorbent properties. The characterization of the superabsorbent revealed a smooth surface with a porous structure, and FTIR analysis showed that chitosan was grafted onto acrylic acid.